Reseña de "Grafología emocional objetiva" de C.A. Honroth - Albornoz, Gladys Susana; Kemerer, Florencia; Vaisman, Facundo; Namujlik, Evelyn; Guevara , Nora; Fernández, Leticia; Centofanti, Alejandro (Minerva, 2023)
Curt A. Honroth (1962). Grafología Emocional Objetiva. Test grafológico emocional. (2da edición). Editorial Troquel. pp. 211.